The efficacy of OK-432 sclerotherapy on thyroglossal duct cyst and the influence on a subsequent surgical procedure. (2nd September 2019) - Tachibana, Tomoyasu; Kariya, Shin; Orita, Yorihisa; Makino, Takuma; Haruna, Takenori; Matsuyama, Yuko; Komatsubara, Yasutoshi; Naoi, Yuto; Nakada, Michihiro; Wani, Yoji; Fushimi, Soichiro; Hotta, Machiko; et al.
Abstract: Background: Although there are studies regarding the efficacy of OK-432 sclerotherapy on thyroglossal duct cyst (TDC), its effects on surgical procedure following this therapy have not been properly described. Objectives: The present study aimed to delineate the prognostic factors of OK-432 sclerotherapy in patients with TDC and investigate its influence on subsequent surgical procedure and the histological characteristics in patients with poor response to OK-432 sclerotherapy. Material and methods: We conducted a retrospective analysis of the medical records of 20 TDC patients treated with OK-432 sclerotherapy. Results: Of the 20 patients, OK-432 sclerotherapy was effective in 5 patients (25.0%). OK-432 showed a lower effective rate in multilocular cysts (9.1%) than in unilocular cysts (44.4%), although not significantly. Five cases were treated with surgery following OK-432 sclerotherapy. There was no significant difference in the operating time and the amount of bleeding between patients with and without OK-432 sclerotherapy. From the results of the histological examination of the cyst wall, two cases had stratified squamous epithelium and two cases showed the absence of lymphocyte infiltration. Conclusion and significance: OK-432 sclerotherapy is an acceptable initial treatment for TDC, especially in unilocular cysts, because of lack of influence on surgical procedure.